Pengaruh Literasi Digital terhadap Pelaksanaan Asuhan Keperawatan - Lestari Hernawati; Rr. Tutik Sri Hariyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This literature study aims to describe the influence of digital transformation on the implementation of nursing care in terms of ethics and the side of providing nursing care. The method used is an integrated literature review method where the source of information is obtained from searching various journals published from 2016 to 2021. Journal searches using the words